Basic income: a radical proposal for a free society and a sane economy - Van Parijs, Philippe; Vanderborght, Yannick (Cambridge, Mass., 2017)
"It may sound crazy to pay people an income whether or not they are working or looking for work. But the idea of providing an unconditional basic income to every individual, rich or poor, active or inactive, has been advocated by such major thinkers as Thomas Paine, John Stuart Mill, and John Kenneth Galbraith. For a long time, it was hardly noticed and never taken seriously. Today, with the traditional welfare state creaking under pressure, it has become one of the most widely debated social policy proposals in the world. Philippe Van Parijs and Yannick Vanderborght present the most comprehensive defense of this radical idea so far, advocating it as our most realistic hope for addressing economic insecurity and social exclusion in the twenty-first century.